Bibliometric Analysis of Watchkeeping Onboard Ships Using Software Vosviewer - Sulistiyowati, Ely; Nurhidayati, Indah; Anita Indriyani, Kristin; Kundori, Kundori (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STIP Jakarta, 2025)
This article aims to conduct bibliometric research on ship crew members who carry out guard duty on ships. Research gaps in watchkeeping studies are identified and analyzed. The method used in this research is descriptive qualitative, namely by describing data visualization. The keyword chosen is